Old dietary cultural practices leading to suboptimal nutritional intake of calories in children with acute viral hepatitis - Bharti, Laxmi Kant; ., Neelu (International Journal of Contemporary Pediatrics, 2020)
Background: Acute viral hepatitis (AVH) is one of the common infections in developing nation. Hepatotrophic virus causes AVH and most of the time it has self-limiting course. HAV is most common cause of AVH. Suboptimal dietary cultural practices are common in our nation. This study was done to know the impact of suboptimal dietary practices done in AVH. Methods: Observational study conducted with 50 children with AVH. Dietary assessment was done at three point of time. First During AVH, second, pre illness and then two weeks after nutritional counselling. Data of dietary modification done by parents/caregiver during AVH recorded. History of herbal medicine taken for treatment of AVH enquired. Results: HAV positive was (72%), HEV positivity was in 8 (16%) cases, hepatitis B was positive in 4 (8%) children and dual infection HAV+HEV was detected in 2 (4%) children. Many parents did dietary modification due to AVH and also by some local treating physicians, 18 (36%) patients were also on herbal medication for treatment of AVH. During AVH the mean calorie and protein requirement decreased from 96% to 54% and 92% to 43% respectively. Two weeks after nutritional counseling the mean calorie and protein intake increased from 54% to 88% and 43% to 84% respectively. This change in calorie and protein was statistically significant (p<0.01) Non-vegetarian diet preference was restarted in many of them after nutritional counseling. Conclusions: This observational study revealed that suboptimal dietary cultural practices are prevalent in India. Majority of children were on bland diet and receiving inadequate proteins and calories.